Fabrication of CO2 Facilitated Transport Channels in Block Copolymer through Supramolecular Assembly - Yao Wang (Polymers, 2014)
In this paper, the molecule 12-amidine dodecanoic acid (M) with ending groups of carboxyl and amidine groups respectively was designed and synthesized as CO2-responsive guest molecules. The block copolymer polystyrene-b-polyethylene oxide (PS-b-PEO) was chosen as the host polymer to fabricate a composite membrane through H-bonding assembly with guest molecule M. We attempted to tune the phase separation structure of the annealed film by varying the amount of M added, and investigated the nanostructures via transmission electron microscope (TEM), fourier transform infrared (FT-IR) etc. As a result, a reverse worm-like morphology in TEM image of bright PS phase in dark PEO/M matrix was observed for PS-b-PEO/M1 membrane in which the molar ratio of EO unit to M was 1:1. The following gas permeation measurement indicated that the gas flux of the annealed membranes dramatically increased due to the forming of ordered phase separation structure. As we expected, the obtained composite membrane PS-b-PEO/M1 with EO:M mole ratio of 1:1 presented an evident selectivity for moist CO2 permeance, which is identical with our initial proposal that the guest molecule M in the membranes will play the key role for CO2 facilitated transportation since the amidine groups of M could react reversibly with CO2 molecules in membranes. This work provides a supramolecular approach to fabricating CO2 facilitated transport membranes.